Public accountability and the public expenditure and financial accountability tool: an assessment - Loozekoot, Andre; Dijkstra, Geske (2017)
Since 2005, the Public Expenditure and Financial Accountability tool has been widely used in developing countries and emerging economies to evaluate the performance of public financial management systems. In this article, we assess the strengths and weaknesses of the Public Expenditure and Financial Accountability instrument tool for evaluating public financial accountability. We examine the theoretical literature on public accountability in order to derive a suitable normative framework to assess the Public Expenditure and Financial Accountability tool. However, given that this literature is based on experiences in developed countries, we must extend it to also take into account the political cultures and practices in developing countries. Using this extended framework, we assess the Public Expenditure and Financial Accountability indicators related to, in particular, parliamentary committees for financial oversight and Supreme Audit Institutions. We conclude that the Public Expenditure and Financial Accountability tool could devote more attention to the independence of Supreme Audit Institutions, the nature of accountability debates, democratic inclusion and horizontal accountability mechanisms. - Reproduced.
Keywords: Public finance; Public administration; Accountability